APPLICATION OF EXPERIMENTAL METHODS AND ASSIGNMENT TO IMPROVE SCIENTIFIC WORK ON COMMUNICATED THE MORPHOLOGICAL CHARACTERISTICS OF GANDARIA (Bouea macrophilla) IN JUNIOR HIGH SCHOOL STUDENTS - Warbanaran, Manselin; Pattipeilohy, Mery; Papilaya, Pamella Mercy (Universitas Pattimura, 2022)
This study aims to determine the improvement of skills in communicated plant morphological characteristics in Junior High School students in Ambon used the application of the experimental method and the method of gived assignments. Find out the differences in the skills of communicating plant morphological characteristics in Junior High School students used the application of the experimental method and used the assignment method. The research used in this study is a qualitative and quantitative descriptive. The subjects of the study were 7th grade students. The samples taked in this study were divided into 12 classes, namely the experimental class, 4 classes, the assignment class, 4 classes and the control class, 4 classes each received different treatment. Data analysis was carried out experimentally. Results were calculated manually and Anacova statistical analysis. The result is a different test or comparative test with the dependent variable having an interval or ratio data scale, while the independent variables consist of a mixture of categorical data and numerical data.